A descriptive investigation and analysis of the 2012 outbreak of B. pertussis in Douglas County, KS - Banfield, Michael (My University, 2013)
The purpose of this report is to present and describe the events which occurred during the 2012 pertussis outbreak in Douglas County, KS. Pertussis, commonly known as whooping cough, is a vaccine-preventable disease. The Lawrence-Douglas County Health Department investigated 305 reported cases and over 900 case contacts. Douglas County experienced the highest incidence in Kansas with a rate of 130.4/100,000 persons. 146 cases were deemed confirmed or probable. This report reviews the management of the disease in Douglas County, vaccination status of reported individuals, a cost estimation of preventative measures, and provides a summary of epidemiological events. Recommendations, based on CDC Public Health Preparedness Capability 13, are included for future outbreak events. These recommendations range from modification of the current reporting tool to encouraging a regular staff meeting.
Keywords: B. pertussis; Public Health; Outbreak; Public Health (0573)